DEVELOPMENT OF THE CONTENT OF POST-GRADUATE PEDAGOGICAL EDUCATION IN THE WESTERN REGIONS OF UKRAINE IN THE SECOND HALF OF THE 20TH – BEGINNING OF THE 21 ST CENTURY - Strazhnikova, Inna (Mountain School of Ukrainian Carpaty, 2023)
Pedagogical work is a vocation, but the effectiveness of this professional activity cannot be achieved without continuous education and the teacher's personal orientation towards self-development and self-improvement. Postgraduate teacher education is a part of continuing education, which is characterized bycertain specificity, aimed primarily at meeting the needs of teachers in the necessary knowledge and skills. The National Doctrine of Education Development specifies that higher and postgraduate education should meet the social and individual needs of educational workers in accordance with global trends in continuous education development. Profound changes in the socio-economic conditions of our society, constant updates in the content of the educational process, emergence of new pedagogical ideas, approaches, technologies, methodologies, the increase in scientific and methodological information, and the introduction of new teaching technologies and forms highlight the need for Ukrainian educators in postgraduate education. This is essential for bridging the gap between the modernization of education and the experience of previous generations. This article provides a historical and pedagogical analysis of the development of postgraduate education content in the western regions of Ukraine from the second half of the 20 th to the beginning of the 21 st century.